2017
DOI: 10.7567/jjap.57.01af03
|View full text |Cite
|
Sign up to set email alerts
|

Improved thermoelectric property of B-doped Si/Ge multilayered quantum dot films prepared by RF magnetron sputtering

Abstract: The use of nanostructured thermoelectric materials that can effectively reduce the lattice conductivity with minimal effects on electrical properties has been recognized as the most successful approach to decoupling three key parameters (S, σ, and κ) and reaching high a dimensionless figure of merit (ZT ) values. Here, five-period multilayer films consisting of 10 nm B-doped Si, 1.1 nm B, and 13 nm B-doped Ge layers in each period were prepared on Si wafer substrates using a magnetron sputtering system. Nanocr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Usenko et al prepared boron‐doped nanostructured bulk Si 80 Ge 20 via a spark plasma technique and reported a low κ t and high ZT value around ~2.9 Wm −1 K −1 and 0.72 at 1073 K, respectively . Yet another example, where Peng et al demonstrated a boron‐doped SiGe thin film and they reported an improved S of 850 μVK −1 at 473 K but their ρ decreased to 1.3 × 10 −5 Ω.m and the PF increased to 5.6 × 10 −2 Wm −1 K −2 …”
Section: High Performance Inorganic Te Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usenko et al prepared boron‐doped nanostructured bulk Si 80 Ge 20 via a spark plasma technique and reported a low κ t and high ZT value around ~2.9 Wm −1 K −1 and 0.72 at 1073 K, respectively . Yet another example, where Peng et al demonstrated a boron‐doped SiGe thin film and they reported an improved S of 850 μVK −1 at 473 K but their ρ decreased to 1.3 × 10 −5 Ω.m and the PF increased to 5.6 × 10 −2 Wm −1 K −2 …”
Section: High Performance Inorganic Te Materialsmentioning
confidence: 99%
“…472 Yet another example, where Peng et al demonstrated a boron-doped SiGe thin film and they reported an improved S of 850 μVK −1 at 473 K but their ρ decreased to 1.3 × 10 −5 Ω.m and the PF increased to 5.6 × 10 −2 Wm −1 K −2 . 475 Another interesting approach to reduce κ lat of SiGe alloy is via different composites. For example, Kikuchi et al embedded SiNWs with a diameter of 10 nm into SiGe 0.3 , where SiNWs were fabricated by the bio-template mask and neutral beam etching techniques, and then deposited by a thermal chemical vapor deposition technique.…”
Section: Sige Alloysmentioning
confidence: 99%
“…In recent years, fruitful research [11][12][13][14] of fabricating QDs by magnetron sputtering have negated the preexisting preconception that the high kinetic energy of particles and the high deposition rate of magnetron ion beam sputtering might induce drastic growth that leads to the formation of polycrystalline islands and the inhibition of the formation of self assembled QDs. Magnetron sputtering is gradually developing into an emerging QD growth technique even though its relevant literatures are still few, and the corresponding obtained evolution mechanism of QDs are still focused on the single-layer structure.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, fruitful research [13][14][15][16] of fabricating QDs by magnetron sputtering have negated the preexisting preconception that the high kinetic energy of particles and the high deposition rate of magnetron ion beam sputtering might induce drastic growth that leads to the formation of polycrystalline islands and the inhibition of the formation of self-assembled QDs. The latest typical work on the growth of multilayer Ge/Si structures by magnetron sputtering was carried out by Peng et al [16], which involved the study of boron-doped Si 1-x Ge x films with multilayer structure of five periods, the work focused on the effects of post annealing on the structure of the samples and the influence of doped atoms on the thermoelectric properties of the samples. Magnetron sputtering is gradually developing into an emerging QD growth technique even though its relevant literatures are still few, and the corresponding obtained evolution mechanism of QDs is still focused on the single-layer structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation